The function of positive face threatening acts baldly on-record without redressive action in household and cyberconflict: a pragmatic study - Sutiadi Rahmansyah; Tajudin Nur; Lia Maulia Indrayani; Davidescu Christiana Victoria Martha (Fakultas Seni Rupa dan Desain ITB, 2020)
Humans as social beings cannot be free from conflict. Speech is one of the causes of conflict. This study discusses the function of Positive Face Threatening Acts on-record baldly without redressive action on household conflicts in a popular psychology book and cyber conflicts between netizens on Facebook. The method used in this research was descriptive qualitative method. The results showed that there were two main functions of the use of Positive Face Threatening Acts baldly on-record without redressive action in household conflicts taken from dialogues in a popular psychology book and cyber conflicts between netizens on Facebook comments, namely if it is used as a utterance then it functions to trigger conflict (PK) and if it is used as a response it serves to maintain FTA/Face/conflict (MK). Whatever the problems or conflicts background that occur both in the household and in the cyber world, conflicts can arise as a result of utterances and also with utterances these conflicts can be resolved or maintained. It depends on the participants involved in the conflict. In other words, utterances can be used either to threaten or defend one's self-esteem/face.